Avaliação da qualidade da água no Território de Identidade do Sisal: um estudo de caso nos principais açudes públicos do município de Teofilândia-BA - Silva, Janderson Oliveira (2017)
Water is essential for the maintenance of life, however, environmental pollution has been causing the loss of the quality of water resources, affecting not only the life of living beings. The reservoirs represent the main source of water to supply the demands of the Brazilian Northeast. However, the quality of stored water has suffered from the effects of anthropic activities makes it compromised for human consumption, animal and for irrigation. In this context, the present work aimed to elaborate a case study on water quality in semi-arid regions, not for human consumption, specifically in the Sisal Identity Territory, having as main study area the main public dams in the municipality of Teofilândia-BA. In order to meet the proposed objective, a mapping of the main water bodies of the municipality of Teofilândia-BA was carried out, using images from Landsat 8 satellite, OLI sensor of 2014, orbit 216/68 by supervised classification. Subsequently, fieldwork was carried out consisting of three (3) campaigns for the collection of surface water, occurring in the period of May (pre-rain), June (post-rain) and November (dry). The physico-chemical parameters and metals analyzed were: Temperature, Salinity, Chloride, pH, OD, BOD, COD, Turbidity, Temotolerant Coliforms, Cadmium, Lead, Copper, Chromium, Manganese, Nickel and were compared with the standards established by Resolution Nº 357 / 2005 of the National Environmental Council - CONAMA. In the evaluation of the results of the Land Use Use map, it was verified that the agricultural culture class predominates in the region with about 44,46%, permanent agriculture (agave) covers 10,72%. The area used with the vegetation (caatinga) is representative, totaling 17,15%. The exposed soil class represents 6,64% and 8,82% of the shade classes. The identifiable water bodies in the satellite image represent 0,16% and 12,05% of urban area. The accuracy of the mapping for the water bodies, provided by the Tau index, was 0,70. Regarding the results of the water quality evaluation of the three public dams located near the urban perimeter in the municipality of Teofilândia-BA during the three campaigns, it was possible to observe that the concentrations of Chloride, Electrical Conductivity, OD, BOD, COD and Thermotolerant Coliforms presented Variations that exceeded the limits established by current legislation. As for the evaluated metals, only Cd was not detected at any point and sampled period. There were no, in their greatest majority, correlation between the variable studies. In the pre-rain period the trend of contamination in the water followed the decreasing order: Ni> Pb> Mn> Cr, in the post-rain: Ni> Pb> Mn> Zn and not dry: Ni> Pb> Cu> Zn. From the data presented, it can be inferred that the main source of pollution of the waters of the dams is derived from anthropogenic origin, mainly by agricultural activities and insufficient sewage network.